1997
DOI: 10.1007/bf01194797
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic gastropexy in the asplenia syndrome

Abstract: The asplenia [Ivemark] syndrome (AS) is the association of congenital absence of the spleen with a variety of visceral abnormalities, predominantly of the cardiovascular system. Varying degrees of malrotation and malfixation of the bowel are common in this condition, and the occurrence of catastrophic gastric volvulus due to malfixation of the bowel has been reported. With the improvement in long-term outlook for these patients with modern cardiac surgery and prophylactic antibiotics, the intra-abdominal anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Excessive coughing may increase intragastric pressure, leading to strangulation of the stomach in a diaphragmatic defect. Other predisposing factors of AGV have been described in the literature, such as asplenia and wandering spleen [14][15][16]. Karande et al described a case of AGV in an 11-year-old boy with Ehlers-Danlos syndrome [6].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive coughing may increase intragastric pressure, leading to strangulation of the stomach in a diaphragmatic defect. Other predisposing factors of AGV have been described in the literature, such as asplenia and wandering spleen [14][15][16]. Karande et al described a case of AGV in an 11-year-old boy with Ehlers-Danlos syndrome [6].…”
Section: Discussionmentioning
confidence: 99%
“…In such rare cases, the gastrophrenic and gastrosplenic ligaments may have supported the intraabdominal organs so that they did not protrude into the thorax. In addition, the presence of pleuroperitoneal adhesions may have played a role in preventing herniation (5, 6). Loss of such physiologic balance may result from a sudden increase in the abdominal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It may be explained by an increased space around the stomach under a left diaphragmatic defect and by laxity of the gastrophrenic and gastrosplenic ligaments. Conditions that increase the intra-abdominal pressure such as excessive coughing or pregnancy may increase the intra-gastric pressure, leading to strangulation of the stomach with a diaphragmatic defect (5, 7). Singh et al (7) reported a diaphragmatic agenesis in an adult similar to our case; a 22-yr-old primigravida (gestation 38 weeks) presented with an acute gastric volvulus and diaphragmatic agenesis was confirmed surgically.…”
Section: Discussionmentioning
confidence: 99%
“…The major causes of mortality and morbidity in situs anomalies are undoubtedly the cardiac malformations that typically occur in these conditions [15]. These are based on the inability of the complex asymmetric connections to develop correctly, and they predictably consist of an ambiguous and single atrium, a single ventricle, and conotruncal anomalies such as truncus arteriosus and transposition [4].…”
Section: Mortality Morbidity and Prognosismentioning
confidence: 99%